Correction: De Felice et al. Development of a Framework for Sustainable Outsourcing: Analytic Balanced Scorecard Method (A-BSC). Sustainability 2015, 7, 8399–8419 - De Felice, Fabio; Petrillo, Antonella; Autorino, Claudio (Sustainability, 2023)
The authors would like to make the following corrections to the published paper [...]